PREVENTION OF PTERYGIUM RECURRENCE BY USING INTRA-OPERATIVE 5-FLUOROURACIL: Prevention of Pterygium Recurrence - Rahman, Lateef ur; Baig, Mushtaq Ahmed; Islam, Qamar ul (Pakistan Armed Forces Medical Journal, 2008)
Objective: This study was aimed to determine the role of intraoperative application of 5-Fluorouracil in the prevention of ptergyium recurrence.Design: A prospective clinical trialPlace and Duration of Study: The study was conducted at Eye Department, Military Hospital, Rawalpindi from February 2000 to August 2001.Patients and Methods: A total number of one hundred and fifty patients were selected for the study and they were divided into two groups on a random basis. Control Group included 75 patients who underwent conventional pterygium excision. 5–Fluorouracil Group included 75 patients who received a single application of 5–Fluorouracil (25 milligram per milliliter) for five minutes immediately after pterygium excision Results: Follow up was conducted in case of both the groups for at least six months. During follow up period, recurrence of pterygia was seen in thirty one patients (41.33%) in the control group while recurrence was seen in 25 patients (33.33%) in the 5-FU group. This shows a slight decrease in recurrence rate (P